Expert Fuzzy Control of Basis Weight Profile in Paper Machines - YAMAMOTO, SHIGEHIKO; SASAKI, TAKASHI; HASHIMOTO, IORI (KAGAKU KOGAKU RONBUNSHU, 1999)
(1) In a paper machine, optimizing control of the basis weight profile based on a process model does not achieve long term continuous running. We have made manual operation of the machine by expert operators into a control algorithm by using membership functions in fuzzy theory, and succeeded in improving the saw tooth profile that is not able to be improved by optimizing control. (2) We have developed an algorithm that defines membership functions of expert fuzzy control using the process interference by slice bolt manipulation. This algorithm makes it possible to apply easily this expert fuzzy control to any type of paper machine.